NOVASOME: A PIONEERING ADVANCEMENTIN VESICULAR DRUG DELIVERY - C.A., ASLAM ABDUL RAHIMAN; KRISHNAN, KARTHIK; A.S., SREELEKSHMI; K.K., ARJUN; NAIR, SREEJA C. (International Journal of Applied Pharmaceutics, 2021)
Pharmaceutical research has developed various new types of innovative forms of drug delivery. Advancement in current drug delivery methods has led to the development of numerous new revolutionary technologies that support safe and efficient formulations over existing ones. Novasome technology is one of the latest liposome developments that have overcome many of the liposomal drug delivery system-related problems. This provides a seven bilayer membrane which is capable of absorbing water-soluble as well as insoluble drugs. The improved efficiency of entrapping drugs with good encapsulation features enables better frequency of dosing, which can be accomplished through the high shear system. These find their applications in diverse fields such as cosmetics, chemicals, personal care, food, pharmacy, and agrochemicals. Several products have already been launched into the market using this technology with an additional launch plan. Due to its depth of penetration, novasomes have been one of the most popular derma cosmetics. It is being studied continuously to obtain improved release characteristics. The prospect of drug delivery and targeting using novasomes is an important area of research and development. This review pinpoints the various aspect of the novasome and will be a milestone for the researchers in the area of drug delivery.